Arduino-Based Light Intensity Measurement - Lathifah, Miqro’ Fajari; Doyan, Aris (AMPLITUDO : Journal of Science and Technology Innovation, 2022)
A concise and factual abstract is required (maximum length 200 words). The abstract Light is a form of energy that is very important and needed by all living things on earth. The intensity of light can be measured using an instrument, namely, Luxmeter. In this study, a light intensity measuring instrument was developed that utilizes electronic components, namely the LDR sensor and Arduino Uno so that it has the same function and working principle as a standard Luxmeter. Based on the test results of the tool, the error rate of the developed light intensity measuring instrument is 2.99% of the standard luxmeter. These results indicate that the developed tool is suitable for measuring light intensity